Socio-Political And Economic Determinants Of Income Inequality In Indonesia - Ichsan Zulkarnaen (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
Income inequality in Indonesia has rapidly enlarged in recent years. This paper aims to examine the causes of highly persistent income inequality in Indonesia. Incontrast to other previous studies that investigated income inequality focusing only on economic factors, this paper also looks at social and political elements. Using Ordinary Least Square (OLS) method, I found that democracy has no significant impact on income inequality. In addition, the study found a significant relationship between government spending and income inequality. In addition, I also found evidence that foreign direct investment (FDI) flows have an impact to improve income inequality in Indonesia. There are several relevant policy conclusions that can be drawn from this study.